2007
DOI: 10.1093/jac/dkl530
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of plasmid and chromosomal glycopeptide resistance determinants occurs more readily in the digestive tract of mice than in vitro and exconjugants can persist stably in vivo in the absence of glycopeptide selection

Abstract: The overall results support the notion that the in vitro model underestimates the transfer potential. Rapid transfer of vanA plasmids from poultry- and pig-derived strains to human faecal E. faecium shows that even transiently colonizing strains may provide a significant reservoir for transfer of resistance genes to the permanent commensal flora. Newly acquired resistance genes may be stabilized and persist in new populations in the absence of antibiotic selection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 44 publications
2
45
0
1
Order By: Relevance
“…Our results are consistent with other demonstrations of the conjugal transfer of resistance genes in gnotobiotic animals in the absence of selective pressure (12,18). In vivo, the ratio of transconjugants per donor was 4 log units higher than in mating experiments on an agar plate.…”
Section: Vol 75 2009supporting
confidence: 92%
“…Our results are consistent with other demonstrations of the conjugal transfer of resistance genes in gnotobiotic animals in the absence of selective pressure (12,18). In vivo, the ratio of transconjugants per donor was 4 log units higher than in mating experiments on an agar plate.…”
Section: Vol 75 2009supporting
confidence: 92%
“…Barbosa et al (3) also observed that the erm34 gene in B. clausii strains was located on the chromosome. Plasmids serve a significant role in the dissemination of antibiotic resistance genes as reported from both in vivo and in vitro studies (9). Thus, plasmid localizations of the observed ermD and ermK genes indicate the potential risk of spreading to other species.…”
Section: Discussionmentioning
confidence: 79%
“…In vitro transfer of vanA plasmids has been determined in a number of studies (Werner et al, 1997;van den Braak et al, 1998;Werner et al, 2010b) and transfer in vivo in digestive tracts of animals and human volunteers was also shown (Moubareck et al, 2003;Lester et al, 2006;Lester and Hammerum 2010). Transfer rates under natural conditions may be higher than determined in vitro (Dahl et al, 2007).…”
Section: Localization and Spread Of Vana-and Vanb-type Resistancementioning
confidence: 99%